The reasons of failed democracy in Belarus - Davidonis, Ramūnas (Politologija, 1999)
Samuel P. Huntington has come to notice that the primary source for the most serious threats to the evolving democracies of the third wave unfold from within, the political leaders and groups, which, once the elections are won and the power—seized, manipulate upon the democratic mechanisms. Hence, when the elected chief executive concentrates the power in his own hands, subordinates or even suspends the legislature, and rules largely by decree, the democratic mechanisms turn first suppressed and later—abolished.By getting a specific shape, Huntington's warning became reality in the Republic of Belarus. On July 10, 1994, the overwhelming majority of Belarus people (80.3%) elected Alexander Lukashenko to become the president of the country. The president reversed the course of democratization and turned the country into authoritarianism. Aimed at meeting the purpose of the article, the author examines the reasons why democracy failed in Belarus.One of these: the failure of democracy came about as a result of inferior and uncompleted economic reforms which made the population face the economic chaos and enormous hardships. The course of events united two forcible segments of Belarus society, which later paved the way for the emergence of Lukashenko—known Soviet nomenklatura and marginalized groups. The goal behind old nomenklatura's actions was its ambition to retain the grip on state property and guarantee access to the market of the Russian Federation. A large part of the population, due to its inability to deal with the new situation caused by economic reforms, chose for the restoration of the old system, in its view—preferably authoritarian, as the way out of the desperate situation.Besides, Belarus stood aloof at the efforts to carry out the political reforms. Therefore, the underdeveloped party system and extremely skeptical attitude of the society towards the rule of law were made dependent on this failure, opening the doors for a populist and charismatic leader to be elected to the highest position, and to illegitimately concentrate powers in his own hands.In addition, the failure of democracy in Belarus can be attributed to weak national identity, frail traditions of democracy, statehood, and civil society. These factors presupposed the fact that Belarus society was yet immature to endorse and implement democracy in their country, the one forced upon them by external circumstances. This phenomenon was later well assessed by Alexander Lukashenko. Once he had become the president, in Belarus no adequate force emerged, which could have canceled the country's future, that of authoritarianism.
Keywords: -